Capa e batina, czyli o tradycjach akademickich Portugalii - Lidia Romaniszyn-Ziomek (Postscriptum Polonistyczne)
The article describes academic traditions in Portugal. They are treated as a social phenomenon, which cannot be compared with Polish academic culture. Praxe académica, that is a variety of rules and habits connected with Portuguese academic life belongs to the life of Portuguese society and is a recognizable element of the Portuguese culture.